Women as carriers of the ‘weaving legacy’: Shifting labour and changing gender relations in marriage - Sayana Basu (International Journal of Educational Research Open, 2024)
The study highlights how women bear the responsibility of perpetuating the cultural identity of the weaving community due to gendered norms around endogamous marriage, the dual burden that women bear within family enterprises, and the exit of male weavers in pursuit of more sustainable economic opportunities. Male weavers of these family enterprises rely on women's continuing allegiance to the ancestral craft to carry forward the economic gains of upholding the weaving craft when they embrace the option of mobility in order to alleviate the financial precarity and stabilise their livelihoods. The normative expectations of marriage within the weaving community, where women's labour is regulated and exploited via intra-community marriage, serve as the foundation for this practice. Women engage in complex negotiations, confront gendered expectations, and, in the worst situations, disrupt gender norms in the family, community, and the labour market throughout this process. The paper drawing from a qualitative study conducted in the handloom clusters of Nadia, West Bengal (India) critically examines the intricate negotiation of gender roles, presenting a nuanced portrayal of how women navigate societal expectations and contribute to reshaping gender norms within family enterprises and weaving community at large.